Genetic diversity among Jatropha curcas L. accessions revealed by RAPD markers - Sahu, Mamta; Kumar, Munish; Akram, Mohd. (Indian Journal of Agroforestry, 2020)
Present study was under taken to assess the genetic relationship between different Jatropha accessions collected from different parts of Uttar Pradesh using RAPD markers. Twenty Jatropha curcas accessions were analyzed using 8 random primers (SBSA series of Genetech Co. Ltd., China) of which 6 produced reproducible polymorphic banding patterns. A total of 59 bands were scored out of which 58.89% were polymorphic. The number of bands generated per primer varied from 3 to 12 bands and a minimum of 3 bands were observed with SBSA-06 primer while the maximum of 12 bands with primer SBSA-04. Both SBSA-02 and SBSA-03 primers amplified unique bands of 900,500 bp in CSJ-38. The results of RAPD analysis of Jatropha curcas accessions revealed that the genetic diversity is very low in the accessions studied which are being cultivated in Uttar Pradesh. This suggests that there is urgent need to widen the genetic base of Jatropha curcas so that the higher yield and oil may be obtained CSJ-38 accession could be utilized for widening the genetic base and improving the yield characteristics. Â